Comparisons of design methods for beam string structure based on reliability and progressive collapse analysis - Sondipon Adhikari (Structures, 2021)
The current design method of ultimate capacity of beam string structure (BSS) is mainly based on the fixed load ratio (FLR) criterion, seldom considers the effect of the random load ratio (RLR) on bearing capacity. This paper compared the coefficient of variation (COV) of bearing capacity obtained by RLR criterion with that obtained by the FLR criterion. It indicates that the random properties of load ratio have a significant impact on COV and should be accounted for. A more realistic limit state function is built with a practical simplification, which is proved to have a better accuracy by reliability verifications for typical cases. Parametric reliability analyses are also carried out with Monte Carlo simulations. The results show that the reliability with FLR criterion is larger than that with RLR criterion. Thus the reliability of BSS would be overestimated following the current design method, and an unsafe design would be resulted in, too. Three targeted reliability indexes are selected for representative cases. Two improved design methods with optimum load and resistance factors are obtained according to minimum differences between the calculated reliability indexes and targeted ones among cases. Finally, the performance of anti-progressive collapse of BSS designed by the two improved methods is compared when the strut or cable fails. The results show that the representative BSS designed by improved design method 2 with fixed load partial factors and optimum resistance factor, which varies with cases, has better performance of anti-progressive collapse.